MORPHOMETRICAL COMPARISONS BETWEEN THE SEXES OF COMMON QUAIL (COTURNIX COTURNIX) IN DISTRICT ABBOTTABAD, KHYBER PAKHTUNKHWA, PAKISTAN - Wajahat Ali; Usama Shafique Dar; Iqra Javed; Hafiz Muhammad Usama (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
District Abbottabad has a nice location, scenic beauty, pleasant weather, and diversity of flora and fauna. There is no morphometrics study available on common quail (Coturnix coturnix) and other avian fauna of the Family Phasianidae in this District. Aim of this study was to provide understandings the morphometrics between the sexes of common quail in this district Abbottabad. Seventy one birds (Coturnix coturnix) were collected in these six months (Februry 2020 to July 2020) from four Tehsils (Tehsil Abbottabad, Tehsil Havelian, Tehsil Lora and Tehsil lower Tanawal) of Abbottabad District. The results revealed, 31 individuals were males and 40 individuals were females. Hunters were contracted for bird collection. Morphometrical comparisons between the sexes showed that the body weight and the body lengths vary significantly. Different parameters value did not differ like bill length, tarsus length, and wing length.